Influence in Economics and Aging - Pavel Jelnov; Yoram Weiss (Institute of Labor Economics (IZA), 2020)
We study the relationship between age and influence in a closed group of 1,000 leading economists. We consider, as a measurement of influence, monthly RePEc rankings. We find that the rankings are not related to age but are related to experience. The optimal level of experience is 30 years from Ph.D. graduation. Additionally, we observe no robust difference in the effect of age and experience between Nobel laureates and leading non-Nobelists. Finally, we find that labor economists enjoy an especially steep improvement in the rankings before they reach the peak; however, the rankings also peak relatively early in their careers.
Keywords: J24; 330; aging; citations; influence; Nobel; research productivity